Resultats de l'evaluation des effets d'un programme de prevention des agressions a caractere sexuel aupres d'eleves de secondaire III au cours de sa phase pilote - Bouchard, Anne-Julie; Bergeron, Manon; Hébert, Martine (Canadian journal of education, 2021)
This study presents the results of a pilot evaluative study of a new sexual violence prevention program designed for high school students. This evaluation is based on a pre-experimental pre-test/post-test design from a sample of 167 high school youths who participated in the classroom workshops. Results show that following their participation in the program, they improved their knowledge, attitudes, protective and supportive skills, and self-efficacy toward sexual violence. This study identifies positive effects following the participation in this program and helps optimize sexual violence prevention initiatives targeting youth.